Advanced ionospheric chirpsounding - Poole, Allon William Victor (Rhodes University, Faculty of Science, Department of Physics and Electronics, 1984)
This dissertation reports research into the theory and practical application of linear frequency modulated ionospheric sounding, as an alternative to the more usual technique of pulse modulation. A comparison of this technique with that of conventional pulse sounders is given, based on the concepts of matched filters and ambiguity functions for both modulations. A theory is developed to relate the group range and phase velocity of the ionospheric target to the phase and frequency of the difference signal at the receiver output. A method is then described whereby the group range and phase velocity of the reflection point as well as the amplitude, arrival angle and polarisation mode of the reflected energy can be measured. A description of the implementation of the technique is given together with some initial results. Finally, some suggestions for improvements are given
Keywords: Ionospheric sounds; Ionosphere -- Research